Entre o “bem viver” e “viver na caixinha” – Conflitos ontológicos no Morro Santana, em Porto Alegre, RS: Between “living well” and “living in a box” – Ontological Conflicts in Morro Santana, Porto Alegre, RS (Simbiótica. Revista Eletrônica, 2023)
This article aims to discuss the multiplicity that constitutes what is known as "Morro Santana," a region in the city of Porto Alegre, Rio Grande do Sul. Through different ontological perspectives – environmental, urban-peripheral, and ancestral Kaingang – we seek to comprehend the complexity of this territory. As part of a broader research process, the study offers preliminary reflections on how territorial, urban, and ecological conflicts can be understood as ontological conflicts. Through this approach, which brings ontological discussions closer to urban issues, the article explores the complex interactions and power dynamics present in Morro Santana. The focus lies on the everyday practices that actively shape the territory, rather than considering it merely as an observed entity.